EUSTATIC EVENTS AND BLACK SHALE SEDIMENTATION AT THE CAMBRIAN-ORDOVICIAN BOUNDARY - Popov L.E.; Koren T.N. (My University, 1996)
The unstable sea-level position in the Cambrian-Ordovician boundary interval resulted in several consequent eustatic minima. Among them, the Lange Ranch (the base of the proavus Zone),Acerocare (the base of the Tremadocian, or beginning of the lindsromi Zone), Black Mountain (the early Tremadocian, or the base of the angulatus/rotundatus Zone), Peltocare (the latest early Tremadocian, near the base of the deltifer Zone) and Ceratopyge (the end of the Tremadocian and the deltifer Zone) events are recognizable in the diverse spectrum of shelf continental facies. The Lange Ranch, Black Mountain and Ceratopyge events were followed by transgressions of different extents, which resulted in a widespread black shale sedimentation in different shelf zones. Paleozoogeographic features and distribution of characteristic litho- and biofacies at the Cambrian-Ordovician and Tremadocian-Arenigian boundaries are analyzed to reveal the possible effect of the climatic factor and the character of biotic changes. The reconstructed paleozoogeography and biofacial zonations are based on trilobites for the Late Cambrian and early Tremadocian, brachiopods for the Arenigian, and graptolites and conodonts for the entire interval discussed.
Keywords: Cambrian; Ordovician; Палеозой::Кембрийская; Paleozoic::Ordovician; Paleozoic::Cambrian; Палеозой::Ордовикская